Impact of the deep squat on articular knee joint structures, friend or enemy? A scoping review - Rojas-Jaramillo, Andrés; Cuervo-Arango, Daniel A.; Quintero, Juan D.; Ascuntar-Viteri, Juan D.; Acosta-Arroyave, Natalia; Ribas-Serna, Juan; González-Badillo, Juan José; Rodríguez-Rosell, David (Frontiers in Sports and Active Living, 2024)
Background: The squat exercise has been shown to improve athletic performance. However, the use of the deep squat has been questioned due to claims that it may cause knee joint injuries. Therefore, the purpose of this scoping review was to synthesize existing literature concerning the impact of deep squats on knee osteoarticular health in resistance-trained individuals. Methods: This study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Scoping Reviews (PRISMA-ScR) guidelines. The original protocol was prospectively registered in Figshare (https://doi.org/10.6084/m9.figshare.24945033.v1). A systematic and exhaustive search was conducted in different databases: PubMed, Scopus, Web of Science, and SPORTDiscus. Additional searches were performed in Google Scholar and PEDro. The main inclusion criteria were the following: 1) Articles of experimental, observational, or theoretical nature, including randomized controlled trials, longitudinal studies, case reports, integrative reviews, systematic reviews, and meta-analyses(Primary studies were required to have a minimum follow-up duration of 6 weeks, whereas secondary studies were expected to adhere to PRISMA or COCHRANE guidelines or be registered with PROSPERO; 2) Peer-reviewed articles published between 2000 and 2024; 3) Publications written in English, Spanish and Portuguese; 4) Studies reporting the effects of deep half, parallel or quarter squats on the knee or evaluating squats as a predictor of injury. Results: The keyword search resulted in 2,274 studies, out of which 15 met all inclusion criteria. These 15 studies comprised 5 cohort studies, 3 randomized controlled trials, 4 literature or narrative reviews, 1 case study, and 2 systematic reviews, one including a meta-analysis. Overall, the risk of bias (ROB) across these studies was generally low. It is worth noting that only one study, a case study, associated deep squats with an increased risk of injury, the remaining 14 studies showed no negative impact of deep squats on knee joint health. Conclusion: The deep squat appears to be a safe exercise for knee joint health and could be included in resistance training programs without risk, provided that proper technique is maintained.